2017
DOI: 10.5603/arm.2017.0052
|View full text |Cite
|
Sign up to set email alerts
|

Cryobiopsy versus Forceps Biopsy in Endobronchial Lesions, Diagnostic Yield and Safety

Abstract: Introduction: This study aimed to evaluate the safety and diagnostic yield of cryobiopsy (CB) in comparison to forceps biopsy in endobronchial lesions. Material and methods:Patients with suspected endobronchial lesions were enrolled. Two forceps biopsies and one cryobiopsy were done in the same patient with randomized sequence. The largest diameter of the samples was measured in mm by electronic caliper. Diagnostic yield of each technique and postbronchoscopy bleeding were evaluated. Results: Samples obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…However, there was also some reported higher incidence of complications of approximately 5% [14] . For some type of procedure such as cryobiopsy, only the incidence of hemorrhage could reach 42.1% [15,16] . Nearly all of these studies concluded that bronchoscopy is well tolerated, but the speci c incidence of complications of different operations has not been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was also some reported higher incidence of complications of approximately 5% [14] . For some type of procedure such as cryobiopsy, only the incidence of hemorrhage could reach 42.1% [15,16] . Nearly all of these studies concluded that bronchoscopy is well tolerated, but the speci c incidence of complications of different operations has not been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…There were no standard criteria for the evaluation of the severity of bleeding during bronchoscopy owing to airway secretion mixed with the blood and di culty to quantify. Therefore, we classi ed the severity of bleeding during the procedure into 4 grades [7,8] : grade 0, no bleeding or extremely minimal bleeding that does not require suction; grade 1, mild bleeding that only requires suction; grade 2, bleeding requiring topical instillation of epinephrine or ice-cold saline; grade 3, moderate bleeding that requires pressure via an in ated balloon catheter or intravenous injection of pituitrin; and grade 4, bleeding requiring hemodynamic support, transfusion of blood products, or interventional or surgical therapy. The severity of bleeding associated with the types of operating procedure was also analyzed.…”
mentioning
confidence: 99%
“…Bleeding is the main side effect of bronchoscopic biopsy in visible endobronchial tumors. No difference has been shown in clinically relevant bleeding between FB and CB in prospective trials [ 39 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…CP has proved to be a valuable addition to the arsenal of interventional pulmonologists and has revolutionized transbronchial and endobronchial biopsies, providing samples comparable to those obtained by surgical means. [1213] The unique freezing property of CP also has facilitated quick evacuation of large endobronchial clots using flexible bronchoscope in patients with respiratory failure. [14] CP has also demonstrated that larger specimens are obtained compared to those by forceps when used for taking parietal pleural biopsies.…”
Section: Discussionmentioning
confidence: 99%